Rousseau on Freedom in Commercial Society. Issue 2 (5th October 2015) - Rousselière, Geneviève
Abstract : Rousseau consistently declares that commercial society prevents us from being free because it makes us dependent on others and on endless desires in ways we cannot control. Yet, in Emile, Rousseau makes the surprising claim that it is possible for an elite to be free in commercial society. This possibility reveals a third way between the model of man and of citizen, that is, the model of natural man in society. I argue that it provides an original way of resisting dependence through a combination of distance from corrupt values and adaptation to the mechanisms of the economic market. Emile's ultimate function, however, is critical in addition to being practical and pedagogical. By following Emile's experiences, the reader learns the unbearably high cost of commercial society: Freedom within it is impoverished and available only to the few.